2010
DOI: 10.1371/journal.ppat.1001116
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Simian Immunodeficiency Virus Infection on Chimpanzee Population Dynamics

Abstract: Like human immunodeficiency virus type 1 (HIV-1), simian immunodeficiency virus of chimpanzees (SIVcpz) can cause CD4+ T cell loss and premature death. Here, we used molecular surveillance tools and mathematical modeling to estimate the impact of SIVcpz infection on chimpanzee population dynamics. Habituated (Mitumba and Kasekela) and non-habituated (Kalande) chimpanzees were studied in Gombe National Park, Tanzania. Ape population sizes were determined from demographic records (Mitumba and Kasekela) or indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
151
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 98 publications
(152 citation statements)
references
References 50 publications
1
151
0
Order By: Relevance
“…However, SIVcpz is also an important pathogen in its own right, since it causes significant morbidity and mortality in its chimpanzee host (6,15,37). Recent natural history studies in Gombe National Park in western Tanzania showed that infected chimpanzees have a 10-to 16-fold increased risk of death compared to uninfected chimpanzees (15).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, SIVcpz is also an important pathogen in its own right, since it causes significant morbidity and mortality in its chimpanzee host (6,15,37). Recent natural history studies in Gombe National Park in western Tanzania showed that infected chimpanzees have a 10-to 16-fold increased risk of death compared to uninfected chimpanzees (15).…”
mentioning
confidence: 99%
“…To screen wildliving populations for SIVcpz infection, our laboratory has developed diagnostic methods that detect virus-specific antibodies and nucleic acids in fecal and urine samples with high sensitivity and specificity (16,41,42). These noninvasive methods, combined with genotyping approaches for species confirmation and individual identification (5,15,37,47,50), have enabled analyses of wild-living chimpanzee populations throughout central Africa. Molecular epidemiological studies have shown that SIVcpz is endemic in both central and eastern chimpanzees, with virus-positive communities identified throughout their habitats (43,44).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, SIVgor could have once been present across a larger geographic area but may have led to the extinction of certain gorilla populations. SIVcpz has been shown to have a substantive negative impact on the health, reproduction, and survival of chimpanzees in the wild, and has caused the decline of at least one chimpanzee community (25,27). Thus, studies on additional infected and uninfected gorilla populations are required to determine the impact of SIVgor on gorilla survival (17).…”
Section: Sivgor In Gorillas Is Less Common and Widespread Than Sivcpz Inmentioning
confidence: 99%
“…Several studies have documented the impact of habitat loss [2][3][4], poaching [5][6][7] and infectious disease [8,9] on wild populations. In Tanzania, 75% woodland vegetation than the closed riverine forest.…”
Section: Introductionmentioning
confidence: 99%